Quality of treatment plans and accuracy of in vivo portal dosimetry in hybrid intensity-modulated radiation therapy and volumetric modulated arc therapy for prostate cancer. Issue 2 (August 2016) - Bedford, James L.; Smyth, Gregory; Hanson, Ian M.; Tree, Alison C.; Dearnaley, David P.; Hansen, Vibeke N.
Abstract: Background and purpose: Delivering selected parts of volumetric modulated arc therapy (VMAT) plans using step-and-shoot intensity modulated radiotherapy (IMRT) beams has the potential to increase plan quality by allowing specific aperture positioning. This study investigates the quality of treatment plans and the accuracy of in vivo portal dosimetry in such a hybrid approach for the case of prostate radiotherapy. Material and methods: Conformal and limited-modulation VMAT plans were produced, together with five hybrid IMRT/VMAT plans, in which 0%, 25%, 50%, 75% or 100% of the segments were sequenced for IMRT, while the remainder were sequenced for VMAT. Integrated portal images were predicted for the plans. The plans were then delivered as a single hybrid beam using an Elekta Synergy accelerator with Agility head to a water-equivalent phantom and treatment time, isocentric dose and portal images were measured. Results: Increasing the IMRT percentage improves dose uniformity to the planning target volume ( p  < 0.01 for 50% IMRT or more), substantially reduces the volume of rectum irradiated to 65 Gy ( p  = 0.02 for 25% IMRT) and increases the monitor units ( p  < 0.001). Delivery time also increases substantially. All plans show accurate delivery of dose and reliable prediction of portal images. Conclusions: Hybrid IMRT/VMAT can be efficiently planned and delivered as a single beam sequence. Beyond 25% IMRT, the delivery time becomes unacceptably long, with increased risk of intrafraction motion, but 25% IMRT is an attractive compromise. Integrated portal images can be used to perform in vivo dosimetry for this technique.